Pemberdayaan Ekonomi dan Ketahanan Pangan Masyarakat Bulupitu melalui Inovasi Smart Eco-Incubator - Marji; Riana Nurmalasari; Erwin Komara Mindarta (Al-DYAS, 2026)
Dependence on natural incubation methods continues to limit the productivity of chicken farming enterprises and efforts to strengthen food security in Bulupitu Village. This community service program aims to empower the local economy and improve community food security through the implementation of the Smart Eco-Incubator innovation to support sustainable chicken farming. This technology was designed with an automatic temperature and humidity control system, an energy-efficient Positive Temperature Coefficient (PTC) heating element, natural thermal insulation materials, and a passive ventilation system. The program implementation included the application of appropriate technology, field trials, and assistance in developing business models and digital marketing. The implementation results showed that the Smart Eco-Incubator increased the egg-hatching success rate to 80–90%, which was higher than the 50–60% achieved through natural incubation methods. The stable microclimate inside the incubator also accelerated the production cycle of high-quality poultry chicks without imposing an excessive electricity cost burden on the community. Post-implementation assistance through the development of independent business models and digital marketing strategies also expanded the market reach of community livestock products. Thus, the integration of environmentally friendly egg-incubation technology and modern business management can increase farmers’ productivity, promote business independence, and strengthen the local economic chain and food security in Bulupitu Village.